The impact of international financial reporting standards on Canadian accounting quality [Impacto de los estándares internacionales de información financiera en la calidad contable canadiense] (2017)
This paper examines whether the application of International Financial Reporting Standards (IFRS) is associated with higher accounting quality in Canada. By using a sample of domiciled and listed companies in the Canadian markets, the change in accounting quality is assessed under two measurement expressions: the value relevance and the level of accounting conservatism. The findings suggest that the accounting information, generated under IFRS, is associated with greater usefulness by market agents; Additionality, the negative returns are incorporated with greater timely in the earnings, regarding to the positive returns. Both results are associated with higher accounting quality. © 2017.